«The life to the emperor, the honour - to nobody»: The moral choice of the Yeugeniy Sergeyevich Botkin (to 140th anniversary of the birthday) - S. G. Ronzhin; A. A. Ryazantsev; I. S. Ronzhin (Бюллетень сибирской медицины, 2006)
Twenty three steps down the basement of the Ipatiev house in Ekaterinburg, the steps into the chasm and the darkness, the movement into the immortality. The moral choice of the last emperor's physician, doctor Yeugeniy Sergeyevich Botkin - it is the choice of the nobleman officer, patriot and the citizen, the choice of autocratic and God-carried Russia romantic. The changes of the governments and epochs as well as of the partialities and the values are possible, but the admiration from the Russian intellectual's soul's force, with his vulnerable conscience is invariable example. The honour - to nobody, never and in spite of any difficulties - the simple and the attractive formula of the doctor's Botkin fate.